Development of Malaria Health Education Model based on Active Learning for Students in the Border Patrol Police Schools, Surin Province, Academic Year 2023 - Punkunkeeree, Sunanta; Veerawongsawat, Kullaya; Maharmart, Sornpet (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2025)
This action research aimed to develop and evaluate a malaria health education model based on active learning for students in Border Patrol Police schools in Surin Province. The study targeted 1,138 students from seven Border Patrol Police schools during the 2023 academic year. A purposive sampling method was used to select 395 students from grades 4–6. The research was carried out in four phases: 1) assessing the current situation and conducting data analysis, 2) designing and developing the educational model, 3) implementing the model, and 4) evaluating its outcomes. Qualitative data were collected through discussions with administrators, health teachers, and officers from Vector-Borne Disease Control 9.3, Surin. Quantitative data were analyzed using frequency, percentage, mean, standard deviation, and dependent t-tests to compare pre- and post-intervention scores on knowledge, perceptions, and behaviors related to malaria. The research developed a malaria health education model based on active learning consisting of three steps: 1) an introduction to the lesson, 2) learning bases, which included the Anopheles mosquito base, prevention and control base, and symptom and treatment base, and 3) a summary of key lessons learned. The evaluation revealed that after implementing the health education model, the average scores for knowledge, perception, and behaviors regarding malaria were 9.27, 12.91, and 10.79 points, respectively. The mean scores for knowledge and behavior before and after the program were significantly different (p < 0.05), while the perception scores showed no significant difference. Administrators, health teachers, and class teachers expressed the highest level of satisfaction with the malaria health education model ( = 4.60, SD = 0.50). Therefore, activities should be enhanced to improve student perception and awareness of malaria, both in school and at home, by utilizing modern media technology and encouraging parental participation in malaria disease surveillance.